Feasibility of using a standardized Caenorhabditis elegans toxicity test to assess nanomaterial toxicity. Issue 5 (25th August 2016) - Hanna, S. K.; Cooksey, G. A.; Dong, S.; Nelson, B. C.; Mao, L.; Elliott, J. T.; Petersen, E. J.
Abstract : Increasing production and use of engineered nanomaterials (ENMs) has generated widespread interest in measuring their environmental and human health effects. Abstract : Increasing production and use of engineered nanomaterials (ENMs) has generated widespread interest in measuring their environmental and human health effects. However, the lack of standardized methods for these measurements has often led to contradictory results. Our goal in this study was to examine the feasibility of using a standardized Caenorhabditis elegans growth and reproduction based toxicity test designed for use with dissolved chemicals to assess ENM toxicity. Sensitivity testing of seven key experimental factors identified by cause-and-effect analysis revealed that bacterial feed density and plate shaking had significant effects on growth inhibition by a reference toxicant, benzylcetyldimethylammonium chloride (BAC-C16). Bacterial density was inversely proportional to experimental EC50 values, while shaking the plates during the assay caused a substantial decrease in nematode growth and reproduction in control nematodes. Other factors such as bacterial viability, organism maintenance, and media type showed minimal effect on the test method. Using this assay with positively charged polystyrene nanoparticles (PSNPs) revealed that the variability in the PSNP EC50 values was larger compared to those of BAC-C16. Additionally, while media type and bacterial viability did not impact BAC-C16 toxicity, PSNP toxicity differed substantially when these parameters were changed. PSNPs were more toxic in K + medium and S-basal compared to M9 and feeding nematodes with UV killed E. coli decreased toxicity of PSNPs. Test validity with ENMs and modifications that can be made to adapt the standard C. elegans toxicity assay for use with ENMs are discussed.